Status and Development of Coal Mine Gas Extraction Technology - Li, Liuyang (International Journal of Natural Resources and Environmental Studies, 2024)
Most of the coal seams in China are geologically old, well closed, with high gas content and high pressure, which are prone to coal and gas protrusion accidents. Coal mine gas extraction technology has been developed for a long period of time, and some extraction pressurization technologies have appeared in improving the effect of gas extraction. And in the research process of low permeability coal seam pressurization technology, hydraulic pressurization technology is gradually applied. In order to solve the problems encountered in the actual production, the development trend of gas extraction technology will be the up-and-down joint extraction, “three-area linkage” three-dimensional extraction, and coal and gas co-mining technology. However, there are some problems in gas extraction, such as theoretical research, extraction technology and popularization and application of technology and equipment, etc., and the research directions are also various